An approximation to social responsibility of the mass media. The case of the commercial radio broadcasting in Perú - Ramirez Lozano, Julianna Paola (2009)
Social responsibility is not a strange concept to the means of communication. Social responsibility in the means of communication, has as a starring point the values that means wants to irradiare in their contents, as well as the fulfillment of its ethic code - if it has institutionalized. In a few words, social responsibility in the means of communication is discovered in the sum of values that means expresses at the momento of spreading information or entertainment, as well as all the planned ser of actions that means rakes in relation to their stakeholders or i nterest groups. However, it is interesting the management analysis of social responsibility in communication companies, beca use means of communication are also companies, so they are supposed ro be profitable, lucrative and socially responsible within the competitive global marker that everydademands more quality standards. A concrete way for which communication companies practice social responsibility is through contents management that seeks to improve the quality of life of objective public whom they address - their main stakeholder. For instance, in the case of commercial radio broadcasting, we can mention the importance that appropriate management of social campaigns managed from contents or social responsibility areas of communication companies. The campaign in the radio succeed in channeling alliances among the most important stakeholders of the media and as a direct benefit, ir provides an answer to each of the stakeholders needs. For example, for listeners, the ítem is resumed in their quality of life improvement, but for the media, in many opporrunities it means the consolidation of the corporative reputation of the company.